Combined effect of cold with heart pathology in old - Sangita, Moirangthem; Keche, Atul; Singh, Anuradha; Poovaragavan, V; Sahoo , Niranjan (Journal of Indian Academy of Forensic Medicine, 2021)
Death due to hypothermia is because of exposure to cold temperature, usually during winter season and at high altitudes. Hypothermia  occurs when the core body temperature drops below 35ᵒC. Diagnosing hypothermia as the cause of death is very challenging in  forensic medicine as the post-mortem findings are not consistent for all hypothermia cases. Therefore, history of the case and  investigation of circumstances of the death, crime scene along with a meticulous post-mortem examination is very important in  diagnosing cause of death as due to hypothermia. Paradoxical undressing and hide and die syndrome can sometime make the crime  scene very suspicious. Hypothermia mainly affects homeless individuals, drug-dependent individuals and those of extreme ends of the  age spectrum but can occur in any age group. Hypothermia is relatively rare in places like India with temperate climates as compared  to places with colder climate. Hence, there is lack of knowledge about such a condition among both the medical professionals and the  common people. Here we report a case of hypothermia in an 82 year old male who was found dead, half naked during the cold winter  season and when stomach was opened, Wischnewsky spots were observed on the mucosa.
Keywords: Hypothermia; Wischnewsky spots; Frost erythema; Meticulous autopsy